Single-cell profiling of CD11c+ B cells in atherosclerosis - Pattarabanjird, Tanyaporn; Srikakulapu, Prasad; Ransegnola, Brett; Marshall, Melissa A.; Ghosheh, Yanal; Gulati, Rishab; Durant, Chistopher; Drago, Fabrizio; Taylor, Angela M.; Ley, Klaus; McNamara, Coleen A. (Frontiers in Immunology, 2024)
Circulating CD11c+ B cells, a novel subset of activated B cells, have been linked to autoimmunity and shown to expand with age. Atherosclerosis is an age-associated disease that involves innate and adaptive immune responses to modified self-antigens. Yet, the expression of CD11c on specific B-cell subtypes and its link to atherosclerosis are poorly understood. In this study, we characterized the frequency of CD11c+ B cells in tissues in mice with aging. We observed an age-associated increase in CD11c+ B cells in the spleen and bone marrow of ApoE−/− mice, and this was associated with an increase in aortic plaque. In addition, we also utilized single-cell multi-omics profiling of 60 human subjects undergoing advanced imaging for coronary artery disease (CAD) to subtype CD11c+ B cells and determine their frequency in subjects with high and low severity of CAD. Using unsupervised clustering, we identified four distinct clusters of CD11c+ B cells, which include CD27 and IgD double negative 2 (DN2), age-associated (ABC), CD11c+ unswitched memory (USWM), and activated Naïve (aNav) B cells. We observed an increase in the frequency of both ABC B cells and DN2 B cells in patients with high CAD severity. Pathway analysis further demonstrated augmentation of autophagy, IFNg signaling, and TLR signaling in DN2 cells in high-severity CAD patients. On the other hand, an increase in the negative regulator of BCR signaling through CD72 was found in ABC cells in low-severity CAD patients. Through investigating scRNAseq of atheroma, these DN2 cells were also found to infiltrate human coronary atheroma.